Influence of Financial Literacy and Frugal Lifestyle on the Concept of Childfree in Childbearing Age Couples (PUS) in West Java - Kartawinata, Budi Rustandi; Akbar, Aldi; Wardhana, Aditya; Citra, Khansa Fairuz (Journal of Business Management and Economic Development, 2024)
Frugal Living or commonly known as a frugal lifestyle is a lifestyle that places a person's consciousness at the highest level when using the money they have while still paying attention to the value of an item. Many people interpret a frugal lifestyle as a frugal lifestyle, which is not wrong, although when it comes to the word frugal, individuals usually put aside the qualities obtained by adopting a frugal lifestyle. Childfree is a term that is often referred to as a concept when married couples decide to choose a life path of not having or raising children. Frugal Living and Childfree are lifestyles that are widely adopted by society, especially young married couples, for the reason that the decision not to have or raise children is because they do not have enough income so that if they have or raise children it will only increase their obligations which will lead to difficulties in managing them. Family finance. These couples of childbearing age (PUS) believe that frugal living is one of their actions by not having or raising children so that their finances can be managed well. Financial literacy is the ability to understand and use a variety of financial skills effectively, including personal financial management, budgeting, and investing. When you are financially literate, you have a basic relationship with money, and it is a lifelong learning journey. The earlier you start, the better off you will be, because education is the key to success when it comes to money. This research seeks to find a relationship between the literacy level of every young couple in Indonesia and the decision to adopt a frugal and childfree lifestyle, especially in West Java Province.